Sprint starts and the minimum auditory reaction time - Pain, M. T. G.; Hibbs, A. (Journal of Sports Sciences, 2007)
The simple auditory reaction time is one of the fastest reaction times and is thought to be rarely less than 100 ms. The current false start criterion in a sprint used by the International Association of Athletics Federations is based on this assumed auditory reaction time of 100 ms. However, there is evidence, both anecdotal and from reflex research, that simple auditory reaction times of less than 100 ms can be achieved. Reaction time in nine athletes performing sprint starts in four conditions was measured using starting blocks instrumented with piezoelectric force transducers in each footplate that were synchronized with the starting signal. Only three conditions were used to calculate reaction times. The pre-motor and pseudo-motor time for two athletes were also measured across 13 muscles using surface electromyography (EMG) synchronized with the rest of the system. Five of the athletes had mean reaction times of less than 100 ms in at least one condition and 20% of all starts in the first two conditions had a reaction time of less than 100 ms. The results demonstrate that the neuromuscular-physiological component of simple auditory reaction times can be under 85 ms and that EMG latencies can be under 60 ms.